2019
DOI: 10.1017/s2045796019000325
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-traumatic stress disorder, depression and somatisation in recently arrived refugees in Germany: an epidemiological study

Abstract: Aims Despite recent worldwide migratory movements, there are only a few studies available that report robust epidemiological data on the mental health in recent refugee populations. In the present study, post-traumatic stress disorder (PTSD), depression and somatisation were assessed using an epidemiological approach in refugees who have recently arrived in Germany from different countries. Methods The study was conducted in a reception facility for asylum-seekers in Leipzig, Germany. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 24 publications
7
111
0
10
Order By: Relevance
“…In contrast, in a study among Kosovar civilian war survivors only 12.9% of participants met the criteria for SOD (56). More similar prevalence rates to our results have been reported in studies of con ict-affected adults in Georgia with 18%, 31% in the Ukraine and a study among refugees recently arrived in Germany with 31% suffering from somatization (15,31,46). In the German general population however, the prevalence of somatization at a moderate to severe level is considerably lower, at 9.3% (57).…”
Section: Prevalence Of Somatic Symptoms and Somatic Distresssupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast, in a study among Kosovar civilian war survivors only 12.9% of participants met the criteria for SOD (56). More similar prevalence rates to our results have been reported in studies of con ict-affected adults in Georgia with 18%, 31% in the Ukraine and a study among refugees recently arrived in Germany with 31% suffering from somatization (15,31,46). In the German general population however, the prevalence of somatization at a moderate to severe level is considerably lower, at 9.3% (57).…”
Section: Prevalence Of Somatic Symptoms and Somatic Distresssupporting
confidence: 86%
“…Among the participants screened positive for depression, 64.8% were also positively screened for somatization. Regarding the participants with PTSD, this rate was as high as 54.7% (15). These ndings suggest that somatization may be an important aspect of trauma, one of the greatest causes of emotional distress (28).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…e Report of the Migrant Integration Policy Index shows that there is still room for improvement in the field of health policy in different countries in the European Union but also in Germany [30]. An additional cost factor is the increased mental health burden within the refugee group [31,32]. One possible strategy for reducing costs was shown by a modelling study in Germany which recommended screening for depression among refugees to identify patients in need of care [33].…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that 56% of the Syrian refugees at Alzatary Camp in Jordan suffered from mental distress, and 46% believed they needed mental support (26). At least 49.7% of the refugees in Germany were screened positive for a mental disorder, with 21.7% having depression and 10.3% having major depression (27). Whilst depression was the most common mental disorder in Sweden with prevalence being 40.2% (28), a study on Syrian school students found that the depression rate was 32% in 2018 (29).…”
Section: Discussionmentioning
confidence: 99%